ANALISIS PENGAKUAN PENDAPATAN DAN PENCATATAN AKUNTANSI PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA BITUNG - Andea, Selint Gar; Sondakh, Jullie J.; Budiarso, Novi Swandari (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
Land and Building Tax is a state tax imposed on land and or buildings in accordance with Law Number 12 of 1994. The purpose of this study is to determine whether revenue recognition and accounting records of PBB-P2 at the Regional Tax and Retribution Management Agency city of Bitung is in accordance with Government Regulation Number 71 Year 2010. This study uses descriptive qualitative research where primary data obtained directly will then be analyzed, so that the results obtained can answer the main purpose of this study. The results show that recognition of tax revenue in Bitung City BPPRD which included, among others, recognition of tax revenue-LRA (Budget Realization Report), recognition of tax-LO income (Operational Report) and recording of PBB-P2 accounting at BPPRD in Bitung, had going well and in accordance with Law Number 71 of 2010.